Analysis of Poverty Alleviation in Tarakan City from the Perspective of Development Theory of Ibn Khaldun - Jaharuddin; Sadiq, Sayyid (Indo Consultan Energi, 2023)
This study aims to analyse poverty alleviation in Tarakan from the perspective of Ibn Khaldun's development theory. This research method uses descriptive qualitative methods, and all data is secondary. The research results show that Ibn Khaldun's development theory can be an idea in carrying out the development of the city of Tarakan by eliminating people's economic difficulties, providing convenience, and creating prosperity. Guarantee the enactment of sharia values ​​that help society instil good qualities towards the balance of resources. Human resource development affects poverty reduction. Wealth does not grow if it is hoarded and stored. It will grow and develop if it is spent for the benefit of society, given to those entitled, and becomes a solution.